До походження бондарихинської культури - Корохіна, А.В. (Археологія, 2009)
На матеріалах керамічного комплексу епонімного поселення показано взаємодію різних за походженням культурних компонентів у процесі формування пам’яток малобудківського типу. Статья посвящена анализу керамического комплекса поселения Малые Будки. Выделены признаки и верхнеднепровского (марьяновского), и волго-окского (поздняковско-раннетекстильного) происхождения. Это позволяет рассматривать процесс формирования бондарихинской культуры как взаимодействие различных по происхождению компонентов без прямой эволюции марьяновской культуры в малобудковский тип. Более очевидна связь его носителей с традициями культур Поволжья. The article deals with the analysis of ceramic assemblage of Mali Budky settlement. Features both of the Upper Dnipro origin (Marianivka), and of the Volga—Oka origin (Late Pozdnyaky — Early Textile) are determined. It allows the author to consider the process of genesis of Bondarykhynska culture as an interaction of various components of different originswithout direct evolution of Marianivska culture into Mali Budky type. A connection of bearers of this type with traditions of cultures of the Volga River region is more obvious.